Determination of a Robust Assay for Human Sperm Membrane Potential Analysis - Baro Graf, Carolina; Ritagliati, Carla; Stival, Cintia; Balestrini, Paula A.; Buffone, Mariano G.; Krapf, Darío (Frontiers in Cell and Developmental Biology, 2019)
Mammalian sperm must undergo a complex process called capacitation in order to fertilize the egg. During this process, hyperpolarization of the sperm plasma membrane has been mostly studied in mouse, associated to its importance in the preparation to undergo the acrosome reaction. However, despite the increasing evidence of membrane hyperpolarization in human sperm capacitation, no reliable techniques have been set up for its determination. In this report we describe human sperm membrane potential (Em) measurements by a fluorimetric population assay, establishing optimal conditions for Em determination. In addition, we have conducted parallel measurements of the same human sperm samples by flow cytometry and population fluorimetry, before and after capacitation, to conclusively address their reliability. This integrative analysis sets the basis for the study of Em in human sperm allowing future work aiming to understand its role in human sperm capacitation.